The Influence of Ineffective Monitoring, Rationalization, and Profitability on Fraudulent Financial Reporting - Nur Anita Chandra Putry; Dewi Kusuma Wardani; Agnes Hardiyanti Dwi Kartika (Universitas KH. Abdul Chalim Mojokerto, 2025)
Financial reporting fraud is widespread among companies in Indonesia and even throughout the world. The high level of fraud in financial reports and the large number of failures in a company raise concerns about the authenticity of a company's financial reports. The research currently being conducted aims to determine the influence of ineffective monitoring, rationalization, and profitability on fraudulent financial reporting. This research method applies a quantitative approach using a sample of 174 manufacturing companies' data on the IDX using sampling techniques, using certain considerations, and analysis of the data using SPSS 25. The independent variables in this research are ineffective supervision, rationalization, and profitability, while the dependent variable is fraudulent financial reporting. Based on the results of data analysis in this research, it was found that ineffective supervision has a significant negative influence on financial statement fraud. In addition, rationalization shows a significant positive influence on financial statement fraud, while profitability has a significant negative influence on financial statement fraud.